Sustainability assessment of food supply chains: an application to local and global bread in Italy - Francesca Galli; Fabio Bartolini; Gianluca Brunori; Luca Colombo; Oriana Gava; Stefano Grando; Andrea Marescotti (Agricultural and Food Economics, 2015)
Over the 2000s', consumers' food purchases have been increasingly informed by supply chain-related issues, with growing concerns about the sustainability of chains differing for their geographical scope. As a result, short food supply chains and local food systems have risen to policymakers and food chain stakeholders' attention as more sustainable alternatives to mainstream food networks. However, associating food chain's geographical scope and sustainability performance may not be straightforward. This paper aims at shedding lights on the connection between geographical scope and sustainability by comparing and discussing 19 attributes owing to different sustainability dimensions. The analysis anchors on the wheat-to-bread chain, due to its global relevance. Bread is a worldwide staple food and wheat is (generally) a commodity traded globally. However, wheat processing often occurs locally and baking is influenced by local heritage and consumption patterns, particularly in the EU and in Italy, where gastronomy is culturally embedded. The paper identifies critical aspects and provides a qualitative assessment of the performances of local vs global wheat-to-bread chains. The assessment is carried out on Italian case studies.
Keywords: Q18; Q10; 330; Sustainability assessment; Food supply chain; Local; Global; Bread